Study on the Buying Motives and Prospects for Small Car Users in Hosur City - N, Priya; Ravi, A (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2016)
Liberalization in 1991. The availability of many alternatives within the city provides an opportunity to the consumers to make a rational decision after considering all the options. Today is an era which is characterized by a consumerâs market where the manufacturers and marketers not only take into consideration the consumer orientation to make them satisfied but goes one step ahead of achieving. Consumer delight. Consumers look for those differentiating parameters, which may help them to make the best decision and can be proved as value to money proposition for them. It makes more important to analyze the consumer perceptions and behavior of the passenger car owners which will give the feedback pertaining to designing the marketing strategies. The objective of this paper is to investigate those differentiating parameter and effect of the reference group that influences the consumer buying behavior of car owners within the city of Hosur.The primary data was collected from 191 respondents, located Hosur in using convenience sampling .The results revealed the strong influence of attributes like price, fuel efficiency in buying decision and importance of reference group.